Cognitive, language and motor developmental patterns of extremely preterm children up to 2 years of age: a descriptive approach - Jurišová, Erika; Ráczová, Lucia; Zaťková, Marta; Romanová, Martina (Frontiers in Psychology, 2025)
BackgroundAdvancements in technology and pharmacology over the past 15 years have increased the survival rates of extremely low gestational age newborns to over 80%. However, these medical achievements are often accompanied by significant challenges in their early and long-term developmental competencies. This longitudinal descriptive study aimed to examine the neurodevelopmental patterns, prevalence of developmental delays, and associated risk factors –gestational age (GA) and birth weight (BW)—in Slovak children born at extremely low gestational age (ELGA), from 7 to 8 months of corrected age to 24–25 months of chronological age, focusing on cognitive, motor, and language development.MethodsThe study included 7 female and 10 male ELGA children with a mean GA of 26.0 weeks (SD = 1.2; range = 24–28) and mean BW of 875.8 grams (SD = 171.2; range = 560–1,150). The Bayley Scales of Infant and Toddler Development, Third Edition (Bayley-III) was administered to assess cognitive, language, and motor development. The developmental functioning of cognitive, linguistic, and motor skills was analyzed using a descriptive approach, based on the average composite scores attained in each domain, in comparison with the normative group defined by the Bayley-III. The developmental patterns of cognitive, linguistic, and motor skills in the observed ELGA children were constructed based on the level of composite scores at two time points: the 7th or 8th month of corrected age (initial assessment) and the 24th or 25th month of chronological age (final assessment). These performance values were classified according to the ‘cut-off’ criteria for developmental delay in the Bayley-III. The degree of delay at these two time points determined the type of developmental pattern.ResultsThe developmental functioning of cognitive, language, and motor skills in the sample of ELGA children studied at the 7th or 8th month of corrected age was within the average range. However, the average scores of ELGA children were 5 to 10 points lower than those of the normative population across domains. At this time point, only 30% of the ELGA children exhibited developmental delay in at least one domain, exclusively at the level of mild to moderate delay (< −1 SD). The prevalence of mild to moderate delay (< −1 SD) was as follows: cognition: 11.7%, language: 11.7%, motor: 29.4%. In the studied sample, we observed a decline in cognitive, language, and motor functioning to the low-average range at 2 years of chronological age. The average scores of ELGA children were 12 to 17 points lower than those of the normative population across domains. At this point, up to 58.9% of the ELGA children exhibited developmental delay in at least one domain. The prevalence of developmental delay was as follows: mild to moderate delay (< −1 SD) was observed in 29.4% of children for cognition, 29.4% for language, and 17.6% for motor skills. Severe delay (< −2 SD) was present in 11.7% of children for cognition, 17.6% for language, and 17.6% for motor skills. In the sample of children with ELGA, we observed declining developmental trends in cognitive and motor skills; however, the values of developmental functioning remained within the range of typical development without developmental delay. Regarding language skills, we observed the most pronounced decline during the first 2 years of development, shifting from typical development to a mild-to-moderate delay (< −1 SD). Within individual domains, we identified four types of developmental patterns in cognitive, language, and motor skills among ELGA children. These patterns were as follows: (1) ascending into the normal range: 0, 5.8, and 11.7%, respectively; (2) stable pattern within the normal range: 58.8, 47.0, and 52.9%; (3) stable pattern within the delayed range: 11.7, 5.8, and 17.6%; (4) descending into the delayed range: 29.4, 41.1, and 17.6%. Findings indicate a higher incidence of developmentally risky patterns in children born at low gestational age (24–25 weeks) and in children with birth weight below 750 grams and lower. Developmental functioning without delay in all three domains (cognitive, language, and motor) was observed in 41.1% of the ELGA children during their second year. The limitation of the study was the small sample size and the absence of Slovak standards for Bayley-III.ConclusionThe results demonstrate significant the need for early and long-term monitoring of developmental trends in this high-risk population, as well as the need to identify a broader range of health and non-health risk factors and their interactions that contribute to their final developmental outcomes.